Marketing en medios sociales y su relación con la comunicación digital de los clientes de la pastelería y panadería “dulsan”, Cantón El Empalme, año 2023 - Montalván Achancí, Génesis Gabriela (2024)
This research project is developed in the context of social networks as a means of marketing for small businesses that have had to adapt to modern digital communication channels. The objective of this study is to analyze the application of marketing in social media and its influence on the quality of communication with the virtual community of the “Dulsan” Pastry and Bakery, El Empalme canton, year 2023. The perception of the experiences was analyzed. online of the company's followers. The methodology applied was qualitative and quantitative to a sample of 368 followers. The qualitative approach consisted of a personal interview with the owner of the business. While in the quantitative approach, an online and physical survey was applied to the company's virtual community and clients. The questions in the questionnaire were rated using a 5-point Likert scale. The data were collected in Excel, processed and tabulated using the SPSS 24 statistical software. The findings demonstrated that the followers of “Dulsan” have a high perception of the variables of valuable content, user experience, quality of communication, engagement, consumer influence and brand recognition. The conclusions describe the favorable acceptance of the audience towards the entrepreneurship, therefore, it is suggested that it strategically manage its profiles on social networks, so that its virtual community becomes loyal consumers.